2021
DOI: 10.3390/jcm10061242
|View full text |Cite
|
Sign up to set email alerts
|

Update on TDM (Therapeutic Drug Monitoring) with Ustekinumab, Vedolizumab and Tofacitinib in Inflammatory Bowel Disease

Abstract: The goal of therapeutic drug monitoring (TDM) is to optimize anti-TNF (tumor necrosis factor) biologic treatment in patients with inflammatory bowel disease (IBD). Although commercial assays are readily available for both ustekinumab and vedolizumab, the use of TDM with these newer biologic medications is at its infancy. The clinical utility of TDM with non-anti-TNF mechanisms of action is not clear. This review summarizes the latest available data on the pharmacokinetics of newer biologic and oral small molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 73 publications
0
22
0
1
Order By: Relevance
“…Endoscopic response is established as a surrogate marker for effective control of CD that predicts a better outcome of the disease [29][30][31]. However, there are a limited number of reports on the association of UST trough levels with endoscopic response in CD patients [32]. As for the ndings in the IM-UNITI maintenance study (mix of 8-or 12-week injections) [17], Adedokun et al reported that the endoscopic remission rate at week 44 was signi cantly higher in patients with a UST trough >0.5 mg/mL than those with ≤0.5 mg/mL, and that the proportion of patients with endoscopic remission reached a plateau at a UST level of 0.5> to ≤1.4 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic response is established as a surrogate marker for effective control of CD that predicts a better outcome of the disease [29][30][31]. However, there are a limited number of reports on the association of UST trough levels with endoscopic response in CD patients [32]. As for the ndings in the IM-UNITI maintenance study (mix of 8-or 12-week injections) [17], Adedokun et al reported that the endoscopic remission rate at week 44 was signi cantly higher in patients with a UST trough >0.5 mg/mL than those with ≤0.5 mg/mL, and that the proportion of patients with endoscopic remission reached a plateau at a UST level of 0.5> to ≤1.4 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with proactive TDM, the utility of reactive TDM has received a greater consensus in guiding therapy for those patients who lost response and where either dose intensification or change to an alternative therapy may be necessary. The utility of reactive TDM have been extended to recently introduced biologics and oral small molecules[ 25 ].…”
Section: To the Editormentioning
confidence: 99%
“…Ustekinumab (UST) is a monoclonal antibody against IgG that affects the immunity of IBD patients by binding to the P40 subunit common to interleukin 12 and interleukin 23. According to a review published in 2021, serum UST concentrations are associated with clinical, biochemical, and histological remissions in most clinical trials[ 8 ]. A multicenter crosssectional observational trial based on 110 CD patients concluded that there was no association between short-term clinical outcomes and UST concentrations[ 9 ].…”
Section: To the Editormentioning
confidence: 99%